BODY SCULPTING (AKA AESTHETIC SURGERY) - AN OVERVIEW - Pandurangan T, (Asian Journal of Medicine & Health Sciences, 2020)
“Beauty is in the eyes of the beholder” Plato – Greek Philosopher (427–347 BCE)“Love of beauty is taste; Creation of beauty is an Art” – Ralph Waldo Emerson (1803–1882)From time immemorial people want to appear more beautiful and attractive. This has two objectives, viz. to attract the opposite sex and second to boost their self-esteem amongst the same sex. This article reviews customs used by people of ancient civilization to beautify themselves along with the modern techniques like Rhinoplasty, Mammoplasty, liposuction, etc., to make oneself more beautiful and attractive.